Mitochondrial and nuclear multilocus phylogeny of Rhipicephalus ticks from Kenya - Kanduma, Esther G.; Bishop, Richard P.; Githaka, Naftaly W.; Skilton, Robert A.; Heyne, H.; Mwacharo, J.M. (Elsevier, 2019)
The morphological diversity of African ticks of the genus Rhipicephalus and subgenus Boophilus have been studied in detail. However, their taxonomy remains poorly resolved with limited molecular studies performed to improve inter-species discrimination. Herein, ribosomal cytochrome c oxidase I (COI), 12S ribosomal DNA (12S rDNA) and nuclear ribosomal DNA internal transcriber spacer 2 (ITS2) were analyzed in Rhipicephalus tick populations in Kenya. While the morphological and molecular criteria separated R. e. evertsi, R. pulchellus and R. appendiculatus from other members of the genus, except the morphologically similar sibling species R. zambeziensis, this was not the case for other tick populations. COI sequences of Rhipicephalus ticks from Ruma National Park (RNP) in Southwestern Kenya, that were morphologically similar to R. praetextatus/R. simus, a formed distinct clade and barcode gap group. 12S rDNA haplotypes of this population were 99% identical to a GenBank accession of R. muhsamae which is thought to be endemic in West and Central Africa. However, the ITS2 locus indicated that the RNP samples were genetically closest to ticks identified morphologically as R. praetextatus. The COI and 12S rDNA haplotype sequences of R. praetextatus clustered closely with R. simus reference sequences though the two species occurred in distinct barcode gap groups. Our results suggest that the R. simus/R. praetextatus/R. muhsamae comprise a closely related tick species complex found across sub-Saharan Africa and includes the yet to be described RNP population. More studies on the biology, ecology and genomics of all life stages of tick species in the complex may clarify their taxonomic status. A continent-wide study that combines morphology, DNA marker sequencing and emerging methods, such as mass spectrometry and whole-genome resequencing may reveal the diversity and distribution of taxa within the genus Rhipicephalus in sub-Saharan Africa.